Nuclear Accidents: Consequences for Human, Society and Energy Sector - L. A. Bolshov; R. V. Arutyunyan; I. I. Linge; I. L. Abalkina (Радиационная гигиена)
The article examines radiation and hygienic regulations with regard to the elimination of consequences of the Chernobyl NPP accident in the context of relationships with other aspects, primarily socio-economic and political factors. This experience is reasonable to take into account when defining criteria in other regulatory fields, for example, in radioactive waste classification and remediation of areas. The article presents an analysis of joint features and peculiarities of nuclear accidents in the industry and energy sectors. It is noted that the scale of global consequences of the Chernobyl NPP accident is defined by the large-scale release of radioactivity into the environment, as well as an affiliation of the nuclear installation with the energy sector. Large-scale radiation accidents affect the most diverse spheres of human activities, what, in its turn, evokes the reverse reaction from the society and its institutions, including involvement of political means of settlement. If the latter is seeing for criteria that are scientifically justified and feasible, then the preconditions for minimizing socio-economic impacts are created. In other cases, political decisions, such as nuclear units’ shutdown and phasing out of nuclear energy, appear to be an economic price which society, as a whole and a single industry sector, pay to compensate the negative public response. The article describes fundamental changes in approaches to ensure nuclear and radiation safety that occurred after the Chernobyl NPP accident. Multiple and negative consequences of the Chernobyl accident for human and society are balanced to some extent by a higher level of operational safety, emergency preparedness, and life-cycle safety. The article indicates that harmonization and ensuring consistency of regulations that involve different aspects of nuclear and radiation safety are important to implement practical solutions to the nuclear legacy problems. The development of regulations on criteria for the classification of radioactive waste and the issues of remediation of radioactively contaminated areas are discussed as the examples.